Eustathii Thessalonicensis De emendanda vita monachica - Eustathius, Archbishop of Thessalonica, -approximately 1194 (Corpus fontium historiae Byzantinae, 2006)
In a detailed account, the archbishop and renowned scholar Eustathius of Thessalonica (probably 1115-1195) takes his monks severely to task, for in his eyes they fall far short of the ideals they professed in their monastic vows, particularly by engaging in business and being hostile to education and learning. With its Prolegomena, editorial work, and indexes, this new edition is a valuable source for Byzantinists. The volume also provides a German translation of the Greek text. In addition to this text, a commentary is published within the series ""Supplementa Byzantina.""Both volumes are availa